Cartografía analógica y digital para la delimitación regional y el análisis temático: aplicación a la cuenca del río Luján (Argentina). - Buzai, Gustavo D.; Lanzelotti , Sonia L.; Paso Viola, Luis Fernando; Principi , Noelia (Revista de Geografía Norte Grande, 2018)
The initial step of the research project “Spatial analysis and evaluation of areas of environmental, productive and patrimonial potential conflicts before the urban expansion in the Luján river basin (Province of Buenos Aires, Argentina)” consisted in updating the delimitation of the study area. In order to carry out this task a theoretical-methodological sequence was drawn up, which involved the analysis of historical cartography, mapping using computer-aided cartography (CAC), definition of boundaries using digital image processing (DIP) through digital elevation models (DEM) and realization of the geographic database through Geographical Information Systems (GIS) linked to Virtual Earth and Digital Globes. The present work presents theoretical and methodological aspects that allow to exemplify the sequence with detail in the high basin area, as much in cartographic aspects as in images obtained in the field work with GPS. The total of the task presents clear aspects of the link between traditional procedures and the current Geographical Information Technologies (GIT) used in the regional construction and thematic representation of the results.